Vulnerabilizing invulnerable: pandemic and the consumption of affluent elderly - Deus, Elisa Priori de (2022)
Consumer vulnerability is a condition that imbalances the consumer-market relationship, causing consumers to lose control of that relationship. The COVID-19 pandemic is an external event that has contributed to this imbalance. This article explains how consumers experience the vulnerability perceived during the pandemic and the role of consumption in dealing with the effects of such vulnerability. We study retired affluent consumers with health and cultural capital to carry out their plans. Interpretative research was conducted through in-depth interviews with 31 Brazilian affluent older people, and other sources were collected, such as memes, journalistic articles, and advertisements. We found that the external event made elderly vulnerable consumers only because of their age. These consumers did not perceive themselves as vulnerable before the pandemic. Also, consumption was revealed as part of the strategy to deal with the consequences of vulnerability, and the market response helped this population resume their feeling of invulnerability.